Impact of the identifiable victim effect on audience willingness to donate to healthcare organizations via Instagram - Konkel, Abby Nicole, author; Tham, Samuel, advisor; Sivakumar, Gaya, committee member; Williams, Elizabeth, committee member (Colorado State University. Libraries, 2023)
The landscape of healthcare fundraising has changed dramatically in recent years due to a rise in online and social media fundraising. As fundraising itself adapts to advancing technology, this study examined how a tried and true traditional fundraising strategy known as the Identifiable Victim Effect impacts audience willingness to donate to healthcare organizations on Instagram. By conducting a 2 x 2 factorial design experimental survey in which photos and captions of Instagram posts were manipulated, the emotional response elicited from different IVE conditions, demographics that may play a role in donating on social media and the ways in which IVE impacts willingness to donate were all examined. This study found that emotional response, measured through Distress and Sympathy positively impacts willingness to donate. This research adds to the existing literature on IVE and starts to bridge the gap that exists at the intersection of healthcare and IVE in social media contexts.
Keywords: identifiable victim effect; fundraising; nonprofit